Indian Fairy Tales - Jacobs, Joseph (Brill | Manohar Publishers & Distributors, 2024)
India is a land of vast ocean of literature written by prominent writers in classical and vernacular languages from ancient times to date. This volume comprises of 14 Indian tales picked from various outstanding classical texts such as Jatakas, Kathasaritasagara, Panchatantra, and various local folklores collected from Punjab, Kashmir, Baluchistan, etc. These tales were translated into English to understand Indian culture and literature. Beneficial for linguists, language experts, and research scholars interested in Indian vernacular tradition.